Oviduct extracellular vesicles protein content and their role during oviduct–embryo cross-talk. Issue 3 (September 2017) - Almiñana, Carmen; Corbin, Emilie; Tsikis, Guillaume; Alcântara-Neto, Agostinho S; Labas, Valérie; Reynaud, Karine; Galio, Laurent; Uzbekov, Rustem; Garanina, Anastasiia S; Druart, Xavier; Mermillod, Pascal
Abstract : Successful pregnancy requires an appropriate communication between the mother and the embryo. Recently, exosomes and microvesicles, both membrane-bound extracellular vesicles (EVs) present in the oviduct fluid have been proposed as key modulators of this unique cross-talk. However, little is known about their content and their role during oviduct-embryo dialog. Given the known differences in secretions by in vivo and in vitro oviduct epithelial cells (OEC), we aimed at deciphering the oviduct EVs protein content from both sources. Moreover, we analyzed their functional effect on embryo development. Our study demonstrated for the first time the substantial differences between in vivo and in vitro oviduct EVs secretion/content. Mass spectrometry analysis identified 319 proteins in EVs, from which 186 were differentially expressed when in vivo and in vitro EVs were compared ( P < 0.01). Interestingly, 97 were exclusively expressed in in vivo EVs, 47 were present only in in vitro and 175 were common. Functional analysis revealed key proteins involved in sperm–oocyte binding, fertilization and embryo development, some of them lacking in in vitro EVs. Moreover, we showed that in vitro -produced embryos were able to internalize in vivo EVs during culture with a functional effect in the embryo development. In vivo EVs increased blastocyst rate, extended embryo survival over time and improved embryo quality. Our study provides the first characterization of oviduct EVs, increasing our understanding of the role of oviduct EVs as modulators of gamete/embryo–oviduct interactions. Moreover, our results point them as promising tools to improve embryo development and survival under in vitro conditions.